Aplicação de boro e maturadores na pré-colheita da cana-de-açúcar em início e final de safra - Siqueira, Gabriela Ferraz de [UNESP] (2014)
The aim, through this study, was to evaluate the effectiveness of foliar application of boron (B), associated or not to the ripeners trinexapac-ethyl, ethephon and sulfometuron methyl in pre harvest of sugarcane, the physiological changes and their implications on quality and stalk yield. This project was composed of three subprojects, the first evaluating the use of B associated with trinexapac-ethyl, the second to ethephon and the third to sulfometuron methyl. For each subproject 4 experiments were carried out at the early and at the late season (2 places and 2 years), so were 12 experiments at early season and 12 at late season, totaling 24 experiments. In the experiments at early season, was used the variety of sugarcane RB855453 (early ripening) in both locations and at late season was used the variety SP80-3280 (late ripening) in Raízen Group and variety RB867515 (middle-late season) in Tereos group. The treatments consisted in the application of the ripeners trinexapac-ethyl, ethephon, sulfometuron methyl and control (natural ripening) associated with the application of B. The doses used were, respectively, 200 g i.e. ha-1 (0,8 L c.p. Moddus ha-1), 480 g i.e. ha-1 (0,66 L c.p. Ethrel ha-1), 0,15 g i.e. ha-1 (0,20 g c.p. Curavial ha-1) and for B the dose was 0,18 kg ha-1 (1060 g boric acid ha-1). Biochemical, biometric, technological and nutritional parameters were evaluated. It was concluded that B deficiency in pre-harvest of sugarcane limits the accumulation of sucrose at early and at late season; at early season the ripeners applied alone or in association with B enabled anticipation in the raw material harvesting in about 15 days and B applied alone was even more efficient, anticipating in about 18 days; at late season the ripeners were effective in maintaining the high sucrose concentration longer than control treatment, as well as B applied alone or in association with ...